Analyses of risks of financial planning on railroads - Olga Kravchenko (Cхід, 2013)
The article substantiates the necessity of considering the current environment of uncertainty in financial planning and forecasting on railroads and are considered the types of risks and the levels of uncertainty that are affected the efficiency of financial planning. Is suggested to use the methodology of scenario planning to improve the quality of long-term and strategic financial plans and forecasts